Dietary lysine centered amino acid density tested across zinc levels in Ross male broilers - M.T. Kidd; S.C. Wells; V.G. Slick; S.K. Orlowski-Workman; K.B. Nelson; K.M. Shafer; A. Jasek (Journal of Applied Poultry Research)
Summary: Broiler nutritionists often increase amino acid density in market conditions where soybean meal price is below average, and breast meat prices are above average. Resultant diets typically have higher lysine levels, coupled with higher levels of other essential and nonessential amino acids and soybean meal. This work assessed dietary amino acid balance across organic Zn source because Zn metabolism spans all known-six enzyme classes and plays a role in protein synthesis. Ross male 708-by-product broilers were fed three Lys-driven amino acid density levels across four added Zn levels in the form of Zn Lys Zn Glu from 1 to 14, 14-28, and 28-42 d of age (12 treatments replicated 6 times). Average dietary digestible Lys ranged from below to above primary breeder guidelines and averaged Zn ranged from 0 to 60 added ppm. Intermediate and total period data consisted of live production, processing transportation weight loss, processing uniformity, processed yields, and subsequent meat quality, of which interactions were minimal, indicating the independency of dietary variables tested herein. Increasing amino acid density improved live performance and breast meat yields, but at the expense of deteriorated meat quality. Higher Zn was needed to improve early livability (1-14 d) and flock uniformity at 42 d. Regarding Lys, feeding broilers 1.30, 1.20, 1.10 % digestible of diet resulted in improved live performance whereas 1.4, 1.3, and 1.2 % digestible resulted in the highest breast yield improvements.